THE BASIS OF JUDGES ‘CONSIDERATIONS ON DECISIONS OF DIFFERENT RELIGIOUS HERITAGE IN ISLAMIC LAW PERSPECTIVE - Junaidi, Junaidi (Nurani, 2020)
Giving inheritance to heirs of different religions is considered a violation of Islamic law, because it is considered not to maintain Islam. property owned by Muslims should be used as a way to worship, not given to non-Muslims. In the settlement of the case of the Pengadilan Tinggi Agama Palembang, decision Number 05/Pdt.G/2015/PTA.Plg, referring to the Yurisprudensi Mahkamah Agung Number: 51K / AG / 1999, which basically states that heirs who are not Muslim can still get assets from the heir Those who are Muslims based on the "WasiatWajibah" which share the same as the part of the daughter of some heirs, so that non-Muslim children are entitled to a share of the inheritance of a Muslim heir as recipients of the obligatory will. What has been decided by the judge to decide the case has deviated from the rules of Islamic law because of the issue of inheritance disputes with Muslim heirs who must comply with the rules of Islamic Inheritance Law.